2019
DOI: 10.18203/2349-3933.ijam20192230
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical profile and etiology ring enhancing lesion in CT scan brain at a tertiary care center

Abstract: Background: Confusion lies over the diagnosis when the patients show ring enhancing lesions of the brain on CT scan. Some consider it as tuberculoma while some consider it as cysticercosis. More studies are required to give clear picture of ring enhancing lesions of the brain. The objective was to study clinical profile and etiology ring enhancing lesion in CT scan brain at a tertiary care center.Methods: This study was conducted in the Department of General Medicine, SVS Medical College, Mahabubnagar district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Hemiparesis was reported as the most common motor deficit (80%), followed by monoparesis (20%) in a similar study by Gandhi and Khalid. 15 Abnormal fundus examination was associated with 36.20% (n ¼ 21/58) of studied participants.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hemiparesis was reported as the most common motor deficit (80%), followed by monoparesis (20%) in a similar study by Gandhi and Khalid. 15 Abnormal fundus examination was associated with 36.20% (n ¼ 21/58) of studied participants.…”
Section: Discussionmentioning
confidence: 90%
“…The incidence of solitary and multiple lesions in the study by Gandhi and Khalid was 90 and 10%, respectively. 15 Similarly, Varma et al reported the incidence of solitary lesions to be 77.1% and multiple lesions to be 22.9%. 14 In the tuberculoma subgroup, 61.76% of patients had multiple discrete RELs, 23.52% had conglomeration, and 14.7% had single RELs.…”
Section: Discussionmentioning
confidence: 94%